Artritis gout dan perilaku dokter keluarga di Kota Manado - Tabalujan, Joice Angela; Palandeng, Henry Malcom Frank; Ottay, Ronald Imanuel (Jurnal Kedokteran Komunitas dan Tropik, 2023)
Background: Untreated hyperuricemia can develop into uric acid-related diseases, such as gout arthritis. Research indicates that 35% of the population in the North Sulawesi Province has elevated uric acid levels. Data from the Social Security Administrative Body for Health (BPJS Kesehatan) in 2022 showed that the number of gout arthritis cases in this province reached 8,781 cases, with Manado City ranked second. This figure increased compared to previous years. According to healthcare procedures, the management of gout arthritis begins at the Primary Health Care (FKTP) such as community health centers and private practice doctors. However, in practice, there are still differences in the approach to gout arthritis management among family physicians, influenced by factors such as their behavior toward disease management. Aim: To assess the overview of behavior (knowledge, attitudes, and practice) of family physicians in the management of gout arthritis in Manado City. Methods: This study is a descriptive study with a cross-sectional research design. Results: The level of knowledge of family physicians in Manado City is considered good by 86% of the respondents, and 14% of the respondents categorized as sufficient The attitude of family physicians was rated as good by 98% of the respondents, and their practice rated as good by 98% of the respondents. Conclusion: The level of behavior of family physicians in the management of gout arthritis in Manado City is considered good.Keywords: behavior; family physicians; gout arthritis